Paleomagnetic and paleoclimatic investigation at Laguna Melincue (Pampean Plains, Argentina): preliminary results - Achaga, Romina Valeria (2017)
Laguna Melincué is a shallow lake located in Santa Fe Province, Argentina (33°41′27.8″S, 61°31′36.5″W). The catchment area is around 1495 km2 and it is located in the Pampean Plains. It was reduced to 678 km2 by the construction of the San Urbano channel in 1941 and reconditioned in 1977, which was built to avoid floods. The floods are related to some El Niño episodes, with high precipitation events. The lake has been previously studied from different approaches, mainly to understand hydrological and climatic variations, but more multidisciplinary studies are needed to understand its complex hydrological situation. Here we present the first paleomagnetic and rock magnetic studies made on a short sediment core collected from the lake in order to contribute to identifying paleoclimatic proxies and to present the first paleomagnetic results for the site. Rock magnetic analyses suggest that the well-preserved magnetic mineralogy is dominated by pseudo single-domain (titano)magnetite and/or maghemite. The results also indicate that a stable characteristic remanent magnetisation can be isolated and thus the directions of the geomagnetic field may be obtained, providing evidence for the use of this lake for paleomagnetic and paleoenvironmental studies. Changes in magnetic grain size and concentration of magnetic minerals suggest environmental variations and changes in the lake level, which are consistent with historical reports. The paleomagnetic results agree well with Cals3k.3 model for inclination and declination of the geomagnetic field except for the dry period probably due to the fact that the core was extracted near the shore.